New records of green (Chlorophyta) and brown algae (Phaeophyceae) for Cabezo Reef, National Park Sistema Arrecifal Veracruzano, Gulf of Mexico - Robinson, Néstor M.; Galicia-García, Citlalli; Okolodkov, Yuri B. (Instituto de Ecología, A.C., 2022)
Descriptions of 13 green and 12 brown algal species from 20 genera and 15 families collected on Cabezo Reef of the National Park Sistema Arrecifal Veracruzano in the southwestern Gulf of Mexico, which are new records for the reef, are given. The species belong to the chlorophyte genera Caulerpa, Cladophoropsis, Codium, Dictyosphaeria, Ernodesmis, Halimeda, Neomeris, Parvocaulis, Percursaria and Rhipocephalus and the phaeophycean genera Canistrocarpus, Colpomenia, Cladosiphon, Dictyerpa, Dictyota, Ectocarpus, Padina, Rosenvingea, Sargassum and Sphacelaria. The family Dictyotaceae contained the largest number of species (6). The descriptions include morphometric and biological data and are accompanied by photographs and line drawings for each species. Data on the geographic distribution in the State of Veracruz, park and the Gulf of Mexico in general are also given. Percursaria percursa is a new record for the park, while Dictyerpa jamaicensis, Sargassum furcatum, Caulerpa racemosa var. occidentalis and Codium isthmocladum subsp. clavatum are new records for the State of Veracruz. Most of the specimens of Chlorophyta were found in the vegetative stage, whereas all the brown algal species except Dictyerpa jamaicensis and Sphacelaria rigidula possessed gametangia or sporangia.